A Surface "Superconvergence" Pathway Connecting the South Indian Ocean to the Subtropical South Pacific Gyre. Issue 4 (20th February 2018) - Maes, C.; Grima, N.; Blanke, B.; Martinez, E.; Paviet‐Salomon, T.; Huck, T.
Abstract: We study the dispersion and convergence of marine floating material by surface currents from a model reanalysis that represents explicitly mesoscale eddy variability. Lagrangian experiments about the long‐term evolution (29 years) of an initially homogeneous concentration of particles are performed at global scale with horizontal current at one fourth degree resolution and refreshed daily over the 1985–2013 period. Results not only confirm and document the five known sites of surface convergence at the scale of individual oceanic basins but also reveal a convergent pathway connecting the South Indian subtropical region with the convergence zone of the South Pacific through the Great Australian Bight, the Tasman Sea, and the southwest Pacific Ocean. This "superconvergent" pathway at the ocean surface is robust and permanent over a distance longer than 8, 000 km. The current variability is crucial to sustain this pathway. Plain Language Summary: Understanding the fate of marine and plastic debris at the ocean surface is an objective to be achieved before informing and discussing with policy and decision environmental makers. The transport pathways of such material need to be precisely determined to estimate the pollution at a global scale. By considering nonstationary ocean dispersion by mesoscale eddy variability, this study reveals a novel convergent zone, over a distance larger than 8, 000 km, that connects the subtropical South Indian Ocean with the core of the convergent zone of the South Pacific Ocean. The existence of a "superconvergent" pathway in addition to the five convergent zones is of interest to scientists studying plastic debris and more broadly to modelers and experimentalists studying ocean physics and biogeochemistry. Key Points: The nonstationary solution of Lagrangian dispersion of floating particles by ocean surface currents is analyzed at global scale A convergent pathway over a distance larger than 8, 000 km, connecting the subtropical South Indian and South Pacific Ocean is revealed and described The variability of the currents is essential to sustain the "superconvergent" pathway